Low-carbon economic dispatching of integrated energy system based on improved white shark algorithm - LI Haobo; CUI Shuangxi; FAN Weijie (Diance yu yibiao)
Aiming at the problem of low-carbon economic dispatching of integrated energy system, this paper considers the synergistic effect of carbon tax and carbon emission economic cost, and establishes a negative impact model of carbon tax on carbon emissions. A low-carbon economic dispatching model of integrated energy system is proposed, which takes the total operating cost and carbon emission of the system as the optimization objective, and takes the energy balance and equipment operation as the constraints. The white shark algorithm is improved by integrating directed differential mutation and other strategies to solve the low-carbon economic scheduling model of the integrated energy system, and the optimal scheduling scheme of each time period is obtained by combining the advantages and disadvantages of the solution distance method. Finally, through the simulation and analysis of standard test functions and calculation examples, it is verified that the performance of the improved white shark algorithm is improved in both convergence and population diversity, and the application of the white shark algorithm in the low-carbon economic scheduling problem of integrated energy system can obtain a more low-carbon economic scheduling scheme.